2002
DOI: 10.1159/000063879
|View full text |Cite
|
Sign up to set email alerts
|

Accommodative Function of Eyes in Persons Exposed to Ionizing Radiation

Abstract: Results of a comparative study of accommodative capability of eyes in individuals exposed to various doses of ionizing radiation and in a control group are presented. The mean values for ranges of accommodation in the control group were consonant with previous data. However, the range of accommodation was found to be reduced in exposed patients from younger age groups. It has been established that the ranges of accommodation depended, besides the age, on the absorbed dose of ionizing radiation: the greater the… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
4
0
1

Year Published

2009
2009
2021
2021

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 10 publications
(5 citation statements)
references
References 3 publications
0
4
0
1
Order By: Relevance
“…Epidemiological studies have provided clear evidence regarding the potential risks of radiation-associated lens changes in the eyes of workers occupationally exposed to IR (Jacob et al, 2010;Vano et al, 2010;Ciraj-Bjelac et al, 2012). It is known that accommodative capability of the eye depends on an individual's age, the absorbed dose, and duration of IR exposure (Sergienko and Fedirko, 2002); in individuals exposed to various doses of IR, it was found to be reduced in younger patients. However, Auvinen et al (2015) reported that the frequency of lens opacities did not increase in physicians with occupational exposure to IR.…”
Section: Discussionmentioning
confidence: 99%
“…Epidemiological studies have provided clear evidence regarding the potential risks of radiation-associated lens changes in the eyes of workers occupationally exposed to IR (Jacob et al, 2010;Vano et al, 2010;Ciraj-Bjelac et al, 2012). It is known that accommodative capability of the eye depends on an individual's age, the absorbed dose, and duration of IR exposure (Sergienko and Fedirko, 2002); in individuals exposed to various doses of IR, it was found to be reduced in younger patients. However, Auvinen et al (2015) reported that the frequency of lens opacities did not increase in physicians with occupational exposure to IR.…”
Section: Discussionmentioning
confidence: 99%
“…7. Individuals from contaminated territories and liquidators had a marked decrease in ocular accommodation (Sergienko and Fedirko, 2002).…”
Section: Ukrainementioning
confidence: 95%
“…Доведено, що у дорослого населення радіаційний вплив спричиняє прискорене старіння органа зору, що виявляється, зокрема, у дозозалежному зниженні акомодаційної здатності [94]. При обстеженні стану ока у дитячого населення радіоактивно забруднених територій, тобто в зонах, де населення зазнає радіаційного впливу у відносно невеликих дозах (найбільшим дозове навантаження було у 1986 році) [95][96][97][98][99] nia risk increase after the prenatal diagnostic X ray in the Jerusalem cohort [86,87].…”
Section: Radiation Cerebro Ophthalmic Effects In Children and In Utero Irradiated Peopleunclassified
“…It has been proven that in the adult population, radiation exposure causes accelerated aging of the visual organ, which is manifested, in particular, in a dose dependent decrease in accommodation capac ity [94]. When examining the condition of the eye in children, radiation contaminated areas, i.e.…”
Section: Radiation Cerebro Ophthalmic Effects In Children and In Utero Irradiated Peoplementioning
confidence: 99%